PWE-244 Does thromboprophylaxis in ulcerative colitis work?: data from the UK IBD audit. (28th May 2012) - Lynch, R W; Roughton, M; Down, C; Arnott, I D
Abstract : Introduction: Venous thromboembolism (VTE) has been long recognised as a complication of inflammatory bowel disease (IBD) with prevalence being reported at between 1.25 and 6.7% and a threefold increased risk being reported when compared to matched cohorts. It has led to recommendations that all patients admitted with acute flares of ulcerative colitis should be given prophylactic subcutaneous heparin although data of efficacy in an IBD population are lacking. We aim to assess the incidence, prophylaxis and possible aetiology of VTE in ulcerative colitis. Methods: We audited 3049 patients with UC. Median age was 42; there were 1421 females and 1628 males. 495 admissions were for elective surgery and there were 2504 emergency admissions of which 882 were considered to have severe disease. 202 Sites audited a median of 18 UC patients per site that were admitted with IBD between 1 September 2009 and 31 August 2010. Data collected contained specific questions on the administration of subcutaneous heparin and whether the patient had a thrombotic event during their admission. We also assessed whether type of admission, age, co-morbidities, disease severity, surgical operations, gender, steroid therapy and treatment response were related to VTE. Results: Of the 3049 patients admitted with ulcerative colitis, 2668 (87.5%) patients were given prophylactic heparin. 66 (2.2%) patients experienced thrombotic events during their admission. The rate of VTE among heparinised patients, 2.2% (59/2668), did not differ significantly when compared to a rate of 1.8% (7/381) within the population who didn't receive prophylaxis (p<0.8). VTE was associated with the need for surgery: 39.4% (26/66) of patients with VTE underwent surgery compared with surgery in 26.2% (781/2983) without VTE (p<0.02). Of these 26 surgical patients within the VTE population, four of these patients' VTE were post-operative. When patients undergoing elective surgery are excluded VTE is associated with co-morbidity: 46.0% (23/50) of the VTE population compared to 32.4% (810/2504) in the non-VTE population (p<0.03). There was no association of VTE with disease severity (severe disease in 42.0% (21/50) with DVT vs 34.4% (861/2504) without VTE, p<0.3) or the use of steroids (steroids used in 96.0% (48/50) with VTE vs 89.6%% (2244/2504) without VTE, p<0.08). Conclusion: Although there was no difference in the frequency of VTE in patients given or not given heparin the numbers of VTE within this group are small. This analysis does however demonstrate that patients with co-morbidity and those undergoing surgery are at higher risk of VTE. Additional measures to prevent VTE should be considered in these patients such as a combination of heparin and compression stockings. All IBD patients admitted to hospital should continue to receive prophylactic subcutaneous heparin. Competing interests: None declared.